2019
DOI: 10.1002/htj.21505
|View full text |Cite
|
Sign up to set email alerts
|

Cu‐water and Cu‐kerosene micropolar nanofluid flow over a permeable stretching sheet

Abstract: This manuscript is a mathematical expression for micropolar nanofluid flow phenomena past a stretching permeable sheet. Here, the micropolar nanofluid, which is water and kerosene based, contains Copper nanoparticles. The similarity approach has been adopted to obtain the ordinary differential equations from the respective basic equations. Using an analytical method, that is, the Adomian decomposition method (ADM), the nonlinear coupled ordinary equations are solved. From the computational aspect, it is ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Recently, Sepasgozara et al [11] have looked forward in their work for a non-Newtonian viscoelastic fluid flow employing DTM and here authors have compared the result with numerical technique also and both results obey with good accuracy. Jena et al [12][13][14][15] found some more related studies on Jeffery fluid flow, viscoelastic fluid flow, and micropolar nanofluid flow where authors have used different methods such as numerical technique, Kummer's function and ADM technique for the solution of non-dimensional governing equations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sepasgozara et al [11] have looked forward in their work for a non-Newtonian viscoelastic fluid flow employing DTM and here authors have compared the result with numerical technique also and both results obey with good accuracy. Jena et al [12][13][14][15] found some more related studies on Jeffery fluid flow, viscoelastic fluid flow, and micropolar nanofluid flow where authors have used different methods such as numerical technique, Kummer's function and ADM technique for the solution of non-dimensional governing equations.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that the use of aluminum oxide‐water nanofluids has a better thermal efficiency of 16% over the pure water. Mohapatra and Mishra 7 used Adomian decomposition method to study the flow characteristics of micropolar nanoliquid over an elongated sheet with radiation effects. The recent developments on this topic can be found in studies reported in References [8‐10].…”
Section: Introductionmentioning
confidence: 99%
“…Exergy is considered as a measure of the quality of energy and its extent of loss by irreversibility in a thermal system. One of the main applications of the exergy concept is the analysis of thermal systems using exergy balances 26‐28 . Exergy dissipation calculations of a transformation indicate the degree of nonreturn.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main applications of the exergy concept is the analysis of thermal systems using exergy balances. [26][27][28] Exergy dissipation calculations of a transformation indicate the degree of nonreturn. Analyzing the effective parameters of this loss can help to understand the role of various factors and explain how they change the process so as to reduce nonreturn, increase efficiency, and ultimately optimize the process.…”
mentioning
confidence: 99%